2022
DOI: 10.22521/edupij.2022.112.5
|View full text |Cite
|
Sign up to set email alerts
|

Did Home-Based Exams during COVID-19 Affect Student Ranking? A Case from a Business School

Abstract: Background/purpose -Home-based exams were introduced during COVID-19 with an open-book format and limited control over dishonest student behavior. Such exams were used in lieu of traditional, closed-book school-based exams as a necessity due to the pandemic. This article investigates whether or not students' grades from home-based assessment exams differed from the grades they achieved in traditional school-based exams.Materials/methods -Using administrative data from 2017 to 2020 from a business school in Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Several studies have not shown any changes in letter grades by moving to home-based exams (Spiegel and Nivetta 2021). Opstad and Pettersen (2022) suggested that a home-based exam favours academically weaker students, who achieve better grades, while for skilled students, it can have the opposite effect. Moore and Jensen (2007) have argued that open-book assessments can lead to more surface learning, while others have suggested that it gives an opportunity to test the higher level of Bloom's taxonomy (Tam 2022).…”
Section: Crt Versus Hbtmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have not shown any changes in letter grades by moving to home-based exams (Spiegel and Nivetta 2021). Opstad and Pettersen (2022) suggested that a home-based exam favours academically weaker students, who achieve better grades, while for skilled students, it can have the opposite effect. Moore and Jensen (2007) have argued that open-book assessments can lead to more surface learning, while others have suggested that it gives an opportunity to test the higher level of Bloom's taxonomy (Tam 2022).…”
Section: Crt Versus Hbtmentioning
confidence: 99%
“…The reason why students experience a school-based test as fairer than a home-based test may be because the latter provides different opportunities for accessing tools, and it can also open the possibility for cheating (Bilen and Matros 2021). This can influence the ranking of students (Opstad and Pettersen 2022). Schoolbased exams ensure equal conditions for everyone to a much greater extent.…”
Section: Crt Versus Hbtmentioning
confidence: 99%
“…A problem with home-based exams is that they are perceived differently, and can tempt many students to unethical behaviour as there is little control (Bengtsson, 2019). This can lead to an unjustified ranking of the students based on knowledge and skills (Opstad & Pettersen, 2022). Management students do not experience this as a problem when choosing individual home-based exams.…”
Section: Anxiety and Fairnessmentioning
confidence: 99%
“…Students are divided in their view of digital readings in relation to traditional teaching and also in terms of which exam forms they think work best, and which provide the best learning outcomes (Bengtsson, 2019;Opstad, 2020a). The choice of exam can have a major impact on the ranking of the students (Opstad & Pettersen, 2022).…”
Section: Introductionmentioning
confidence: 99%